Smart Temperature and Humidity Monitoring pada Data center Dinas Komunikasi dan Informatika Daerah Istimewa Yogyakarta berbasis Raspberry Pi 5 dan Notifikasi Discord - Widiyatmoko, Ari; Suharjo, Imam (Jurnal Kridatama Sains dan Teknologi, 2025)
A data center is a vital component of Information and Communication Technology (ICT) infrastructure that requires continuous physical environmental monitoring, particularly for temperature and humidity. These parameters significantly affect the stability and longevity of server equipment. Therefore, a monitoring system with high accuracy, reliability, and rapid response capability is essential. This study aims to design and develop an integrated temperature and humidity monitoring system using a Raspberry Pi 5 as the control unit, employing a DHT22 sensor to measure environmental conditions. The collected data is stored in a MariaDB database, visualized through a Grafana dashboard, and complemented with automated notification delivery via the Discord platform. The implementation and testing were conducted at the Data center managed by the Department of Communication and Informatics of the Special Region of Yogyakarta. The system supports real-time monitoring, alerts when environmental parameters exceed defined safety thresholds, and automated daily reports sent to a designated Discord channel. The research follows an engineering-based system development method, comprising stages of literature study, needs analysis, system design, implementation, testing, and evaluation. The testing results indicate that the system performs accurate sensor readings (within a tolerance range of ±0.4°C for temperature and ±1.4% for humidity) and successfully stores data periodically in the database. It also reliably sends automatic alerts to Discord when temperature or humidity levels exceed the specified thresholds (18–27°C and 30–60% RH) and delivers visual dashboard reports twice daily on a schedule. This monitoring system is expected to support the operational team of the Data center in managing environmental security more effectively and responsively